Taxonomic study of the protecta-group in the genus Pagaronia Ball (Hemiptera, Cicadellidae, Evacanthinae) from Japan - Kamitani, Satoshi; Higuchi, Toshiyuki; Okudera, Shigeru (Zootaxa, 2012)
Seven species, including three new species, of the protecta-group in the genus Pagaronia Ball are recognized from Honshu,Japan. Pagaronia totoumiensis sp. nov., P. dichotoma sp. nov. and P. lanceolata sp. nov. are described from central Honshu.Some intraspecific morphological variations of P. protecta Okada, P. tridens M.Hayashi & Arai and P. spinosa Y.Hori are analyzed. Additional localities for all the described species of this species-group are also given.